Deep-level defects in CdSe/ZnSe QDs and giant anti-Stokes photoluminescence - Valakh, M.Ya.; Sadofyev, Yu.G.; Korsunska, N.O.; Semenova, G.N.; Strelchuk, V.V.; Borkovska, L.V.; Vuychik, M.V.; Sharibaev, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
CdSe/ZnSe structures with a quantum dot extrinsic photoluminescence band related to the defects that contain vacancies in cation sublattice has been investigated. It is shown that such defects can be localized in different parts of heterostructure (inside ZnSe barrier and cap layers, Zn₁-xCdxSe wetting layer and at quantum dot heterointerface) and their localization depends on the preparation regimes and parameters of investigated structures. It is shown that defect level follows the heavy-hole related level. An intense anti-Stokes photoluminescence of quantum dots has been found. Two-step excitation mechanism of the anti-Stokes photoluminescence through the local states of investigated defects localized on the quantum dot interface is proposed.